MODEL RANTAI PASOK DAN RANTAI NILAI JAMBU KRISTAL PT KREASI TANI BUMIAJI KOTA BATU - Itroh Adinda; Etty Soesilowati; Sugeng Hadi Utomo (JURNAL AGRIMANSION, 2025)
This study aims to analyze the structure and mechanism of the supply chain and value chain of the crystal guava commodity at PT Kreasi Tani Bumiaji in Kota Batu using a mixed-method approach. The study encompasses mapping the flows of products, information, and finance, as well as analyzing marketing margins and farmer’s share as indicators of efficiency and value distribution along the supply chain. The findings reveal that the supply chain operates in an organized and efficient manner with active involvement from partner farmers, PT Kreasi Tani BumiAji, modern retail, and cooperatives. Marketing margins and farmer’s share are influenced by the length of the distribution channels and the complexity of the marketing network. Product diversification strategies through processing into processed products effectively address the issue of excess supply and enhance added value. These findings underscore the importance of integrated supply chain and value chain management in supporting the competitiveness of horticultural products while improving the welfare of partner farmers.